Step
*
1
1
2
2
3
1
of Lemma
DAlembert-equation-iff3
1. f : ℝ ⟶ ℝ
2. ∀x,y:ℝ.  ((x = y) 
⇒ ((f x) = (f y)))
3. ∀x,y:ℝ.  (((f (x + y)) + (f (x - y))) = (r(2) * (f x) * (f y)))
4. u : ℝ
5. r0 < u
6. g : (-(u), u) ⟶ℝ
7. h : (-(u), u) ⟶ℝ
8. d(f x)/dx = λx.g x on (-(u), u)
9. d(g x)/dx = λx.h x on (-(u), u)
10. r0 < (h r0)
11. ¬¬((∃c:ℝ. ∀x:ℝ. ((f x) = rcos(c * x))) ∨ (∃c:ℝ. ∀x:ℝ. ((f x) = cosh(c * x))))
12. ∀c:ℝ. ((∀x:ℝ. ((f x) = rcos(c * x))) 
⇒ rfun-eq((-(u), u);λ2x.c * -(c * rcos(c * x));λ2x.h x))
13. ∀c:ℝ. ((∀x:ℝ. ((f x) = cosh(c * x))) 
⇒ rfun-eq((-(u), u);λ2x.c * c * cosh(c * x);λ2x.h x))
14. x : ℝ
15. c : ℝ
16. ∀x:ℝ. ((f x) = rcos(c * x))
17. -(c * c) = (h r0)
⊢ (f x) = cosh(rsqrt(h r0) * x)
BY
{ ((Assert r0 ≤ -(c * c) BY
          Auto)
   THEN (Assert c = r0 BY
               (BLemma `square-is-zero` THEN Auto THEN BLemma `rleq_antisymmetry` THEN Auto))
   ) }
1
1. f : ℝ ⟶ ℝ
2. ∀x,y:ℝ.  ((x = y) 
⇒ ((f x) = (f y)))
3. ∀x,y:ℝ.  (((f (x + y)) + (f (x - y))) = (r(2) * (f x) * (f y)))
4. u : ℝ
5. r0 < u
6. g : (-(u), u) ⟶ℝ
7. h : (-(u), u) ⟶ℝ
8. d(f x)/dx = λx.g x on (-(u), u)
9. d(g x)/dx = λx.h x on (-(u), u)
10. r0 < (h r0)
11. ¬¬((∃c:ℝ. ∀x:ℝ. ((f x) = rcos(c * x))) ∨ (∃c:ℝ. ∀x:ℝ. ((f x) = cosh(c * x))))
12. ∀c:ℝ. ((∀x:ℝ. ((f x) = rcos(c * x))) 
⇒ rfun-eq((-(u), u);λ2x.c * -(c * rcos(c * x));λ2x.h x))
13. ∀c:ℝ. ((∀x:ℝ. ((f x) = cosh(c * x))) 
⇒ rfun-eq((-(u), u);λ2x.c * c * cosh(c * x);λ2x.h x))
14. x : ℝ
15. c : ℝ
16. ∀x:ℝ. ((f x) = rcos(c * x))
17. -(c * c) = (h r0)
18. r0 ≤ -(c * c)
19. c = r0
⊢ (f x) = cosh(rsqrt(h r0) * x)
Latex:
Latex:
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  ((f  x)  =  (f  y)))
3.  \mforall{}x,y:\mBbbR{}.    (((f  (x  +  y))  +  (f  (x  -  y)))  =  (r(2)  *  (f  x)  *  (f  y)))
4.  u  :  \mBbbR{}
5.  r0  <  u
6.  g  :  (-(u),  u)  {}\mrightarrow{}\mBbbR{}
7.  h  :  (-(u),  u)  {}\mrightarrow{}\mBbbR{}
8.  d(f  x)/dx  =  \mlambda{}x.g  x  on  (-(u),  u)
9.  d(g  x)/dx  =  \mlambda{}x.h  x  on  (-(u),  u)
10.  r0  <  (h  r0)
11.  \mneg{}\mneg{}((\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  ((f  x)  =  rcos(c  *  x)))  \mvee{}  (\mexists{}c:\mBbbR{}.  \mforall{}x:\mBbbR{}.  ((f  x)  =  cosh(c  *  x))))
12.  \mforall{}c:\mBbbR{}.  ((\mforall{}x:\mBbbR{}.  ((f  x)  =  rcos(c  *  x)))  {}\mRightarrow{}  rfun-eq((-(u),  u);\mlambda{}\msubtwo{}x.c  *  -(c  *  rcos(c  *  x));\mlambda{}\msubtwo{}x.h  x))
13.  \mforall{}c:\mBbbR{}.  ((\mforall{}x:\mBbbR{}.  ((f  x)  =  cosh(c  *  x)))  {}\mRightarrow{}  rfun-eq((-(u),  u);\mlambda{}\msubtwo{}x.c  *  c  *  cosh(c  *  x);\mlambda{}\msubtwo{}x.h  x))
14.  x  :  \mBbbR{}
15.  c  :  \mBbbR{}
16.  \mforall{}x:\mBbbR{}.  ((f  x)  =  rcos(c  *  x))
17.  -(c  *  c)  =  (h  r0)
\mvdash{}  (f  x)  =  cosh(rsqrt(h  r0)  *  x)
By
Latex:
((Assert  r0  \mleq{}  -(c  *  c)  BY
                Auto)
  THEN  (Assert  c  =  r0  BY
                          (BLemma  `square-is-zero`  THEN  Auto  THEN  BLemma  `rleq\_antisymmetry`  THEN  Auto))
  )
Home
Index